Review on potential phytocompounds in drug development for Parkinson disease: A pharmacoinformatic approach. (2016) - Vijayakumar, S.; Prabhu, S.; Rajalakhsmi, S.; Manogar, P.
Abstract: Parkinson's disease (PD) is caused by human physiological function and is ranked as the second most common neurodegenerative disorder. One of the prominent therapies currently available for PD is the use of dopamine agonists which mimic the natural action of dopamine in the brain and stimulate dopamine receptors directly. Currently, available pharmaceutical drugs provide only temporary relief of the disease. Phytocompounds have been identified as promising target of research in the quest for new pharmaceutical compounds as they can produce secondary metabolites with novel chemical structure. In this review the drug development of Parkinson disease has been analyzed using computational tools.